DEVELOPMENT OF MUNICIPAL SERVICES ПРОГРАММЫЭНЕРГОПОТРЕБЛЕНИЯ UKRAINE THROUGH INNOVATIVE METHODOLOGY OF - , А. Ю. (Municipal economy of cities. Series: «Economy science», 2013)
The possibility of applying innovative management methodology for the formation of a more efficient system of energy consumption in the communal area.